"Value congruity’’ is it important for word of mouth? - I Nyoman Andika Putera Yasa; Ardhan Hilfiyanda; Johannes Dimson Marbun; Husna Leila Yusran (Enrichment : Journal of Management, 2022)
This study is among the first few attempts to examine the impact between different dimensions, namely, cognitive, affective and activation dimensions of CBE and Self Identification with value congruity as a intervening variable. This study improves to understanding of WOM communication.This research was conducted to examine the effect of value congruity influence of customer brand engagement, self identification, on word-of-mouth (WOM).This research uses purposive sampling with multiple regression and data were analyzed using SPSS. The results revealed that three dimensions of CBE had a positive impact on self-identification with value congruity as a intervening variable ; self identification also had a positive impact on WOM communication.The model was tested in the context of e-service sector; future research may investigate in different context and consider to added new variable according to the existing context.